Phase 1 study of safety, tolerability and immunogenicity of the human telomerase (hTERT)-encoded DNA plasmids INO-1400 and INO-1401 with or without IL-12 DNA plasmid INO-9012 in adult patients with solid tumors. Issue 7 (6th July 2021) - Vonderheide, Robert H; Kraynyak, Kimberly A; Shields, Anthony F; McRee, Autumn J; Johnson, Jennifer M; Sun, Weijing; Chintakuntlawar, Ashish V; Pawlicki, Jan; Sylvester, Albert J; McMullan, Trevor; Samuels, Robert; Kim, Joseph J; et al.
Abstract : Background: Human telomerase reverse transcriptase (hTERT) is frequently classified as a 'universal' tumor associated antigen due to its expression in a vast number of cancers. We evaluated plasmid DNA-encoded hTERT as an immunotherapy across nine cancer types. Methods: A phase 1 clinical trial was conducted in adult patients with no evidence of disease following definitive surgery and standard therapy, who were at high risk of relapse. Plasmid DNA encoding one of two hTERT variants (INO-1400 or INO-1401) with or without plasmid DNA encoding interleukin 12 (IL-12) (INO-9012) was delivered intramuscularly concurrent with the application of the CELLECTRA constant-current electroporation device 4 times across 12 weeks. Safety assessments and immune monitoring against native (germline, non-mutated, non-plasmid matched) hTERT antigen were performed. The largest cohort of patients enrolled had pancreatic cancer, allowing for additional targeted assessments for this tumor type. Results: Of the 93 enrolled patients who received at least one dose, 88 had at least one adverse event; the majority were grade 1 or 2, related to injection site. At 18 months, 54.8% (51/93) patients were disease-free, with median disease-free survival (DFS) not reached by end of study. For patients with pancreatic cancer, the median DFS was 9 months, with 41.4% of these patients remaining disease-free at 18 months. hTERT immunotherapy induced a de novo cellular immune response or enhanced pre-existing cellular responses to native hTERT in 96% (88/92) of patients with various cancer types. Treatment with INO-1400/INO-1401±INO-9012 drove hTERT-specific IFN-γ production, generated hTERT-specific CD4+ and CD8+ T cells expressing the activation marker CD38, and induced hTERT-specific activated CD8 +CTLs as defined by cells expressing perforin and granzymes. The addition of plasmid IL-12 adjuvant elicited higher magnitudes of cellular responses including IFN-γ production, activated CD4+ and CD8+ T cells, and activated CD8+CTLs. In a subset analysis of pancreatic cancer patients, the presence of immunotherapy-induced activated CD8+ T cells expressing PD-1, granzymes and perforin correlated with survival. Conclusions: Plasmid DNA-encoded hTERT/IL-12 DNA immunotherapy was well-tolerated, immune responses were noted across all tumor types, and a specific CD8+ phenotype increased by the immunotherapy was significantly correlated with survival in patients with pancreatic cancer.